Exon 2 containing myelin basic protein (MBP) transcripts are expressed in lesions of experimental allergic encephalomyelitis (EAE) - Nagasato, Kunihiko (J Neuroimmunol, 1997)
Exon 2 containing myelin basic protein (MBP) transcripts are expressed during developmental myelination in mice and humans, and during remyelination subsequent to virally induced demyelination in adult mice. Since remyelination characterizes CNS lesions during experimental allergic encephalomyelitis (EAE) and multiple sclerosis (MS), we investigated whether exon 2 containing isoforms of MBP are expressed in EAE lesions during relapsing disease. Exon 2 containing MBP transcripts were detected by in situ hybridization in 17 of 52 EAE mice and in 16 of 30 mice at the peak of the first or second episode of paralysis. Thus exon 2 containing MBP transcripts are expressed in lesions of the CNS during active phases of chronic relapsing autoimmune disease. Implications of these findings with respect to future therapies aimed toward enhancing remyelination in EAE and, possibly MS, are discussed.